Impact of the Revolution´s Programs in Cienfuegos Dental Services - Beatriz García Alpízar; Mikhail Benet Rodríguez; Emma Gil Ojeda; Yumaidy Colina Sánchez (Medisur)
Background: Revolution´s Programs in Stomatology are part of a strategy to improve oral health of the population and the quality of the dental services. Objective: To asses the impact of Revolution´s Programs in the primary dental services in Cienfuegos. Methods: Retrospective, longitudinal study evaluating the tendencies of dental services markers of municipalities of Cienfuegos before and after the intervention between 2000 and 2007. Results: The effectiveness in Stomatology services improved in more than 100% in 2007 compared with 2005; the good use of prosthesis increased in 100%; the assistance covering and resolution index for persons over 60 years and bellow 19 increased lineally, reaching values similar to those of the first years of the studied period. Conclusions: The impact of the Revolution’s Programs was positive since the performance of the studied markers was superior after the intervention.